The Lives of Women in Militarized Zones - Ocasiones*, Leny G. (Philippine Social Sciences Review; Vol 58 No 1: Jan 2006-Dec 2007, Ed. Jorge V. Tigno, 2009)
Militarization has always been the response of the Philippine government to the age-old insurgency in the country. Yet very few studies have been conducted to document the lives of women who are trapped into such stressful and violent situations. This paper is an offshoot of a study conducted in rural Cebu, which is considered the hotbed of rebellion in the province and consequently, militarized. It reveals that militarization has profound and unique impacts on women, distinct from those of men, as strong patriarchal beliefs and practices prompt military and paramilitaries to use symbolics of gender differences and women’s subordination in their strategies, leading women to experience militarization differently than men. It also explores the similarities and differences of the structural violence of poverty and exclusion experienced by women before and after militarization. Militarization compounds the economic, social, and cultural exclusion of women, making it harder for them to fulfill meaningful productive and reproductive roles in their daily lives. At the same time, far from being passive recipients of violence and intimidation, the women in the study reveal agency and capacity to become sole breadwinners of their families and defenders of their communities, challenging long-held patriarchal assumptions in Philippine society that women are weak and passive and men are dominant and in charge of family life. __________ * Faculty member of the Department of Sociology and Anthropology at the University of San Carlos in Cebu City. Email: locasiones@yahoo.com.
Keywords: women, militarized zone